Assessment of reported in-patient adverse events: retrospective study of reported adverse events at the Free State Psychiatry Complex from 2008-2010 - Qhali, Jacoline Martha (My University, 2015)
Background: Although the Free State Psychiatry Complex has collected information on adverse events, the reporting processes have not been consistent, systematic or transparent and this information was not used in the planning process. In addition, there is also a perception that the rate of adverse events is increasing, that these adverse events are not managed adequately and the extent of the problem could not be determined. It was for this reason that this study was found to be necessary to investigate further on patterns of serious adverse event occurrence, to put the argu-ments to a scientific test and be certain about the extent to which contributory factors were associated with the occurrence of these events in the Free State Psychiatry Complex. Aim: The aim of the study was to describe the inpatient-related adverse events and factors contributing to these adverse events reported at the Free State Psychiatry Complex in order to develop effective strategies to prevent and reduce these ad-verse events. Methodology: This was a cross sectional study design based on a retrospective re-view of records of patients who were involved in these adverse events. The study was undertaken at Free State Psychiatric Complex which is a specialized Mental Health Care Establishment from 1 April 2008 to 31 March 2010. All records of re-ported adverse events of all inpatients at Free State Psychiatry Complex were re-viewed and no sampling was done. The study included review of routinely collected hospital information on patients’ records and registers and from the Advance Incident Management System (AIMS). Results: There were 419 Serious Adverse Events reported during 1 April 2008 to 31 March 2010. The most commonly reported SAE’s included Aggressor-Aggressor, Aggression-victim, Behaviour/Human Performance, Accident/occupational health and safety and falls. The Aggression related adverse event type was one of the most common types of SAE’s, constituting 40% of the Serious Adverse Events reported. The Behaviour /Human Performance adverse event type was second in frequency. Other common SAE’s reported during the study period included Medication, Pres-sure ulcer, Clinical Management and Organisation Management. These Serious Ad-verse Events occurred in 5% of the inpatients at Free State Psychiatry Complex and the findings showed an increase rate of 3.3%. Although more than 80% of the ad-verse events gave rise to moderate disability, 2% caused permanent disabling inju-ries and 2% led to death. However, only 15% of the SAE’s caused minor harm to pa-tients. The most Serious Adverse Events occurred in the months of March, Decem-ber and November which indicate that seasonal changes are associated with in-creased risk for Serious Adverse Events. Most SAE’s happened during the day-shift which might be ascribed to the organisational routines such as medication rounds, handover periods and mealtimes. Human and System Adverse Event Error Types accounted for more than 70% of these SAE’s. The study revealed a positive relationship between the patients in the Intellectual disability and Psycho-geriatric specialities and Accident/occupational health and safety as well as falls related adverse event types. There was also a posi-tive correlation between male patients in the age group of 9-38 in the Acute and Fo-rensic Specialities and Aggression- as well Behaviour Performance related Adverse Event Types. The patients diagnosed with Schizophrenia, Substance Induced Psy-chosis and Intellectual Disability was mostly associated with an increased risk for Se-rious Adverse Events. The results showed that co-morbidity, the patient’s disease profile, age, admission classification, organisational routines and seasonal changes are associated are contributory factors too Serious Adverse Events. It supports the premise that human and system errors as well as the profile of the patient are con-tributing to SAE’s. Conclusion: Safety issues in mental health are unique and are in that way different to the safety issues in medical care. Both the patient population and the environment make patient safety in mental health unique. The uniqueness is associated more with the diagnosis, the patient population and with the mental health setting. SAE’s included Aggressor-aggression, Aggressor-victim, Behavior Performance (abscond-ing, self-harm, suicide); Occupational health and safety, falls and other injuries are particularly prominent to mental health patients. Although patient safety in mental health was considered a field of importance, there is still a lack of awareness of the issues as well as a shortage of research and readily available information to guide patient safety systems, practices, policies, and care delivery in mental health. Work is required to establish a clear definition, set priorities, and develop strategies for re-sponding to patient safety concerns. Models of quality improvement are being uti-lized in psychiatry hospitals but the need for evidenced-based quality improvement models for inpatient psychiatric care still exist. Findings from my study showed that Serious Adverse Events are prevalent in Free State Psychiatry Complex and factors significantly associates with the frequency of aggression-, behavior/occupational health and safety and falls related adverse event types. Advancing a quality and safety research agenda for inpatient psychiatric care will guide practice, improve care, and help ensure efficient and effective care. Complicated problems such as the provision of acute psychiatric hospital services require solutions that incorporate depth of understanding the complexities of acute mental illness as well as changes in prevailing attitudes and systems. This study has also highlighted that Serious Adverse Events are contributed by a varied set of contributing and interacting elements, including patient factors, human factors, system factors, and environmental factors. A complex interaction between the mental health environment and the diagnosis/patient population was found which differentiates patient safety from other health sectors is. Understanding this interac-tion and its relationship to patient safety is very important. It is believed that research in scientific advances, systems analysis, education and development, dissemination of guidelines and improved standard of practice is required for reduction of SAE’s (Leappe et al. 1991) This was the first study to systematically evaluate adverse events in a mental health establishment in the Free State province. The researcher hopes that the Department of Health in the Free State Province would utilise the findings of this study to review and to improve the safety programmes on the care, treatment and rehabilitation of the mental health care services.
A RESEARCH REPORT SUBMITTED TO THE FACULTY OF HEALTH SCIENCES, UNIVERSITY OF THE WITWATERSRAND, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF PUBLIC HEALTH IN THE FIELD OF HOSPITAL MANAGEMENT Johannesburg, September 2014
Keywords: Hospitals, Psychiatric; Risk Assessment